2019
DOI: 10.14744/nci.2019.24855
|View full text |Cite
|
Sign up to set email alerts
|

Our clinic’s first experience with HoLEP

Abstract: OBJECTIVE:The present study reports a retrospective evaluation of the first Holmium laser prostate enucleation (HoLEP) cases and their results in our clinic.METHODS:Twenty four patients who underwent HoLEP surgery between April 2017 and November 2017 were evaluated for demographic characteristics, duration of operation, amount of hemorrhage, amount of energy used, tissue weight removed, catheterization time and complications. IPSS and uroflowmetry results were compared before and after the surgery.RESULTS:Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Similarly, it is equally effective as TURP for smaller prostates with the lowest complications rates [10,15,16]. Holep significantly improves Qmax and reduces LUTS, all of which have been proven in many reports [17][18][19]. As a result of the learning curve, Holep-associated complications such as prostate capsular perforation or bladder mucosal damage are likely to occur more frequently when the procedure is newly implemented, but decrease with time and experience [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is equally effective as TURP for smaller prostates with the lowest complications rates [10,15,16]. Holep significantly improves Qmax and reduces LUTS, all of which have been proven in many reports [17][18][19]. As a result of the learning curve, Holep-associated complications such as prostate capsular perforation or bladder mucosal damage are likely to occur more frequently when the procedure is newly implemented, but decrease with time and experience [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…All patients except one had complete enucleation of their prostates in one session. In Turkey, a research team reported a morcellated prostate volume of 29.2 ± 11 ml [11], while another team reported that the resected adenoma volume was 52.3 ± 8.3 ml [29]. In South Korea, a sonographically calculated resected prostate tissue volume of 29.2 ± 20.1 ml [30] was reported in keeping with our observation that prostates we see in Nigeria or Africa presenting for surgery are much bigger than those seen in several other continents.…”
Section: Discussionmentioning
confidence: 99%